Working the interdisciplinary integration: Assesing a bridge activity between two subjects of Environmental Sciences Degree - M. Sandín Vázquez; X. Lazo Vitoria; M. Giménez Baldazo; M. Rodríguez Martínez (Red U, 2016)
This paper describes how an interdicisciplinar group of teachers implements a bridge-activity between two subjects in 2nd course of Environmental Sciences degree. The main goal is to develop both generic and specific competencies related to interdisciplinary work. Students evaluate if these innovation proposals are adequate to develop these skills and what impact produces in their own learning. As main conclusion, to note that coordination between teachers to interconnect subjects within degrees is a very appropriate intervention to provide students with a comprehensive education and skills, they value these activities very positively.